Linguistics in people with disabilities - Ugarte Rodríguez, Filiberto (2004)
This article emphasizes the importance of studying the various aspects of the language of people with disabilities, because with the results of such studies we could understand more clearly some language phenomena that are controversial or have been little studied to date.